2008
DOI: 10.1103/physreva.77.022303
|View full text |Cite
|
Sign up to set email alerts
|

Efficient vibrational state coupling in an optical tilted-washboard potential via multiple spatial translations and application to pulse echoes

Abstract: We measure the application of simple and compound pulses consisting of time-dependent spatial translations to coupling vibrational states of ultracold 85 Rb atoms in a far-detuned 1D optical lattice. The lattice wells are so shallow as to support only two bound states, and we prepare the atoms in the ground state. The lattice is oriented vertically, leading to a tilted-washboard potential analogous to those encountered in condensed-matter systems. Experimentally, we find that a square pulse consisting of latti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…For the lowest few levels, superconducting qubits of the transmon [15], phase qubit [19], and capacitively shunted flux qubit [16] types are well approximated by a SNO. Furthermore, motional states in optical lattices [24], collective modes of ion traps [26] and nanomechanical oscillators [34] are also described as SNOs.…”
Section: A Lab Frame Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…For the lowest few levels, superconducting qubits of the transmon [15], phase qubit [19], and capacitively shunted flux qubit [16] types are well approximated by a SNO. Furthermore, motional states in optical lattices [24], collective modes of ion traps [26] and nanomechanical oscillators [34] are also described as SNOs.…”
Section: A Lab Frame Hamiltonianmentioning
confidence: 99%
“…In fact, it has been shown that no physical particle can be a true qubit [23]. Examples of leakage states include higher vibrational states in optical lattices [24], polarized spin states in the singlet-triplet qubits [25], and auxiliary states in ion traps [26] and Rydberg atoms [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Here E R = 2 k 2 L /2m is the recoil energy, i.e., the kinetic energy the atom gains by absorbing a lattice photon. At these lattice depths for typical atomic densities the atoms are essentially non-interacting [11] and thus we can simplify the model by considering the evolution of a single atom.…”
Section: A Modelmentioning
confidence: 99%
“…We consider a physical model of the optical lattice similar to the experimental apparatus described in Refs [11,31,32]. The optical lattice potential is generated by two vertical counter-propagating lasers with an incidence angle of 49.6 • and is loaded with 85 Rb atoms from an optical molasses at 10 µK.…”
Section: A Modelmentioning
confidence: 99%
See 1 more Smart Citation